Spiking neural network equalization for IM/DD optical communication - Arnold, Elias; Böcherer, Georg; Müller, Eric; Spilger, Philipp; Schemmel, Johannes; Calabrò, Stefano; Kuschnerov, Maxim (Arxiv, 2022)
A spiking neural network (SNN) equalizer model suitable for electronic neuromorphic hardware is designed for an IM/DD link. The SNN achieves the same bit-error-rate as an artificial neural network, outperforming linear equalization.
Version 1 vom 9 Mai 2022, Version 2 vom 1 Juni 2022
Gesehen am 17.10.2022